Safety and efficacy of a feed additive consisting of lactic acid produced by Weizmannia coagulans (synonym Bacillus coagulans) DSM 32789 for all animal species except for fish (Jungbunzlauer SA). (29th April 2022) - ,; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of lactic acid produced by a non‐genetically modified strain of Weizmannia coagulans (synonym of Bacillus coagulans ) (DSM 32789) for all animal species except for fish. The production strain qualifies for the QPS approach for safety assessment. Although uncertainty remains concerning the possible presence of viable cells and/or spores of the production strain in the final product, this does not raise safety concerns for the target species, humans and the environment. The lactic acid is safe at 50, 000 mg/kg complete feed for functional ruminants and pigs and at 20, 000 mg/kg feed for all the other animal species and categories except for pre‐ruminants for which a safe level cannot be established. The corresponding safe levels in water for drinking would be 15, 000 mg/L water for pigs and 8, 000 mg/L for other non‐ruminant species. Although no safe concentration of lactic acid in water for drinking for ruminants can be derived, the Panel considers that the use in water for drinking is safe in ruminants when the total daily intake of the additive does not exceed the daily amount that is considered safe when consumed via feed. The use of the additive under assessment in animal nutrition is considered safe for the consumers and for the environment. It is considered corrosive to the skin, eyes and mucous membranes. Lactic acid is used in food as a preservative. It is reasonable to expect that the effect seen in food will be observed in feed when it is used at comparable concentrations and conditions. However, the FEEDAP Panel has reservations about its effectiveness as a preservative in complete feed with a moisture content of ≤ 12%.